Associations between obesity, smoking behaviors, reproductive traits and spontaneous abortion: a univariable and multivariable Mendelian randomization study - Wang, Qingyi; Liu, Fanglei; Tuo, Yinfeng; Ma, Li; Feng, Xiaoling (Frontiers in Endocrinology, 2023)
Background The correlation between potential risk factors such as obesity (leg fat percentage (left), arm fat percentage (left), waist circumference, body fat percentage, trunk fat percentage), smoking behaviors (past tobacco smoking, smoking initiation, smoking/smokers in household, current tobacco smoking) and reproductive factors (age first had sexual intercourse (AFS), age at menarche (AAM), and age at first birth (AFB)) have been linked to the occurrence of spontaneous abortion (SA). However, the causal associations between these factors and SA remain unclear. Methods We conducted univariable and multivariable Mendelian randomization (MVMR) analyses to evaluate the associations of obesity, smoking behavior and reproductive factors with SA. To select appropriate genetic instruments, we considered those that had reached genome-wide significance level (P < 5 × 10–8) in their corresponding genome-wide association studies involving a large number of individuals (ranging from 29,346 to 607,291). SA was obtained from the FinnGen consortium, which provided summary-level data for 15,073 SA cases and 135,962 non-cases. Results Assessed individually using MR, the odds ratios (ORs) of SA were 0.728 (P=4.3608×10-8), 1.063 (P=0.0321), 0.926 (P=9.4205×10-4), 1.141 (P=7.9882×10-3), 5.154 (P=0.0420), 1.220 (P=0.0350), 1.228 (P=0.0117), 0.795 (P=0.0056), 1.126 (P=0.0318), for one standard deviation (SD) increase in AFS, AAM, AFB, smoking initiation, smoking/smokers in household, arm fat percentage (left), leg fat percentage (left), waist circumference and body fat percentage, 0.939, (P=0.3075) and 1.075 (P=0.1479) for one SD increase in past tobacco smoking, trunk fat percentage for one SD increase in SA. In MVMR, only AFS (OR = 0.802; P = 0.0250), smoking initiation (OR = 1.358; P = 0.0080), waist circumference (OR = 0.813; P = 0.0220) and leg fat percentage (left) (OR = 4.446; P = 0.043) retained a robust effect. Conclusion This research provides evidence for the independent causal roles of AFS, waist circumference, leg fat percentage (left), and smoking initiation in the occurrence of SA.